A low concentration of choline chloride alters the developmental program of the bovine preimplantation embryo - McKenzie L J Haimon; Eliab Estrada-Cortés; Thiago Fernandes Amaral; Jeremy Block; Surawich Jeensuk; Tatiane S Maia; Quinn A Hoorn; Masroor Sagheer; João H Bittar; Peter J Hansen (Bioscientifica, 2024)
Choline is a known developmental programming agent of the bovine preimplantation embryo. Culture of the embryo with 1.8 mmol/L choline, a concentration much higher than in blood, alters development to cause increased weaning weight and other changes during the postnatal period. It was hypothesized here that choline exerts similar effects on the developmental program of the embryo when added at concentrations similar to those in peripheral blood (i.e. 4 μmol/L). Oocytes were collected via ovum pickup, and embryos were produced in vitro. Embryos were cultured until day 7 after fertilization in medium with 4 μmol/L choline chloride or, as a vehicle control, with an additional 4 μmol/L sodium chloride. Blastocysts were transferred into recipients, and pregnancy was diagnosed at approximately 28 days of gestation. Subsequent calves (n = 37 for vehicle and n = 35 for choline) were weighed at birth and at weaning. Addition of choline to the culture medium did not affect the proportion of embryos that became blastocysts or the proportion of transferred blastocysts that produced a pregnancy. Birth weight was unaffected by treatment, but calves derived from choline-treated embryos were heavier at the time of weaning and gained more per day from birth until weaning than calves derived from embryos treated with vehicle. Results demonstrate that choline can act on the preimplantation embryo at a physiologically relevant concentration to alter postnatal phenotype. Observations are further evidence for the importance of the first days of embryonic development for the phenotype of the resulting calf. Lay summary The period of early embryonic development is one in which changes in the environment of the embryo can alter its development and affect characteristics of the resultant offspring. Here, we show that providing a nutrient called choline to the cow embryo for the first 7 days of development increased growth after calving. These results suggest that it may be possible to program embryonic development early in pregnancy to improve livestock production.